The Relationship Between The Age Of Maternity Mothers And The Incidence Of Uterine Atony At Dr. H. Bob Bazar Hospital Skm Kalianda South Lampung - Muji Lestari; Weni Guslia Refti; Andriansyah, Andriansyah; Yurita Mailintina (Sean Institute, 2024)
Uterine atony is the most common cause of early postpartum hemorrhage (50%) and is often the main reason for having a postpartum hysterectomy. Uterine contractions are a key mechanism in controlling bleeding after childbirth. Atonia occurs when this mechanism fails. Physiologically, postpartum hemorrhage is controlled by contraction of myometrial fibers surrounding blood vessels leading to the area of placental implantation. Uterine atony occurs when these myometrial fibers do not contract. The purpose of this study was to understand the characteristics of maternity mothers who experienced uterine atony at Dr. H. Bob Bazar Hospital, SKM Kalianda South Lampung in 2024. The research method used was quantitative with a cross-sectional design involving 30 respondents. Research Results: there is a relationship between the age of postpartum mothers and the incidence of uterine atony at Dr. H. Bob Bazar Hospital SKM Kalianda South Lampung with a p-value of 0.000.